KEMAMPUAN OLAH TUBUH MAHASISWA PRODI PENDIDIKAN TARI UNIVERSITAS LAMPUNG BERDASARKAN INDEKS MASSA TUBUH - Dewi, Mirnawati; Lestari, Goesthy Ayu Mariana Devi; Wendhaningsih, Susi (Jurnal Seni dan Pembelajaran, 2025)
AbstractThis study aims to determine the physical movement ability of students in the Dance Education Study Program based on Body Mass Index (BMI). The data used in this research is primary data collected from students of the Dance Education Study Program at the University of Lampung from the 2021 and 2023 cohorts, with a total sample of 24 students. The approach used in this study is descriptive quantitative, which aims to process and analyze the data obtained from the research subjects. Data collection was conducted through BMI measurements, practical tests on 12 lifting techniques, and interviews. The analysis technique employed is descriptive statistics using mean calculations to comprehensively describe the results.The findings indicate that students classified as overweight had an average score of 51.1 with a grade of D, which falls into the low category. Students classified as underweight obtained an average score of 64 with a grade of C+, which is categorized as moderate. Meanwhile, students with a normal BMI achieved an average score of 69.1 with a grade of B, which is considered high. This study provides insights into the relationship between BMI and students' physical movement abilities in the dance education program, serving as an evaluation and development reference for improving the quality of body movement courses in the future.Keywords: physical movement ability, students, body mass index.